TRANSFORMATION OF COMMUNITY INFORMATION GROUP POJOK JATIROGO: FROM INFORMATION MEDIA TO INTEGRATED MARKETING COMMUNICATION AND DIGITAL SERVICES: TRANSFORMASI KOMUNITAS INFORMASI MASYARAKAT POJOK JATIROGO: DARI MEDIA INFORMASI KE KOMUNIKASI PEMASARAN TERPADU DAN LAYANAN DIGITAL - Angel Pramitasari; Harliantara; Nuránnafi FSM (LPPM Stikosa - AWS, 2025)
Digital transformation has reshaped the way communities access information and services, including through the role of Community Information Groups (KIM). This study explores the transformation of KIM Pojok Jatirogo from a community-based information medium into a facilitator of integrated marketing communication and a provider of digital services. The objectives are to describe the transformation process, analyze communication strategies, and evaluate the impact on local economic empowerment. A descriptive qualitative approach was employed, involving in-depth interviews, participant observation, and document analysis. The findings reveal that KIM Pojok Jatirogo successfully integrated public information functions with digital services such as PJEK Delivery, Digiplain Digital Marketing, and Tour & Travel. Operational data indicate substantial growth: PJEK orders increased from 622 per month in 2018 to more than 4,000 per month in 2025, while MSME supported by Digiplain grew from 5 in 2019 to 300 in 2025. By applying Integrated Marketing Communication (IMC) strategies that combine WhatsApp, Facebook, Instagram, Tik Tok and offline events, KIM enhanced both community engagement and UMKM competitiveness. These findings reinforce Diffusion of Innovation theory (Rogers, 2003) and the social capital concept (Putnam, 2000), highlighting the importance of change agents and trust networks in the success of community-based innovation. This study concludes that community-driven digital transformation strengthens local economic ecosystems and enhances KIM’s legitimacy as a strategic partner of local government. The scientific contribution lies in offering a replicable model of community-based integrated marketing communication with implications for MSME development and rural digital economy building.